Geographical distribution of protected cultivation in Amarah district (Journal of the College of Basic Education, 2023)
Protected agriculture in Maysan Governorate in general and Amarah district in particular aims to develop agricultural production as well as the use of modern irrigation methods in agriculture such as the drip irrigation method, as well as meeting the needs of agriculture and farmers, addressing their agricultural problems, increasing the productivity of agricultural crops, and meeting the needs of society for food security. To study the natural factors that affect agricultural production, the researcher concluded through the field study that the expansion and development of this agriculture can contribute to filling the market's need for various main vegetables